Explicitation in legal translation — a study of Spanish-into-Danish translation of judgments - Anja Krogsgaard Vesterager (JoSTrans: The Journal of Specialised Translation)
This article reports on the findings of an empirical study on Danish translators' use of explicitation in their translations of an excerpt from a Spanish judgment. The aim of the study was to examine: (1) whether Danish translators use explicitations in their translations of a judgment from Spanish into Danish, and (2) whether differences can be observed in relation to the participants' expertise in translation. To fulfil the purpose of the study, an experiment involving translation from Spanish into Danish was performed. The data — a Spanish source text and 10 translations into Danish by five experts and five non-experts — were analysed using qualitative methods followed by a quantitative synthesis. The analyses focussed on explicitations in relation to the items of nominalisations, passives, system-bound terms, and elliptical phrases. The results of the study showed that explicitations did occur in the target texts and that experts explicitated more than non-experts. In addition, the results revealed differences between experts and non-experts in the units they explicitated. While experts opted for explicitations in relation to all of the focal points, non-experts only explicitated system-bound terms and elliptical phrases.